Design, synthesis and biological evaluation of bioorganometallic metallarectangles - Golding, Taryn (Department of Chemistry, 2022)
Malaria is a devastating mosquito-borne disease, characterized by high levels of morbidity and mortality. The absence of a suitable vaccine to offer protection and the emergence of drug-resistant parasite strains continues to be the driving force behind the development of new antimalarial agents. Cancer, which is the second leading cause of deaths globally, accounted for a estimated 9.6 million deaths in 2018. Despite tremendous advances made within the field of drug discovery, the past four decades of cancer chemotherapeutic treatment has largely depended on platinum-based drugs (e.g. cisplatin and its derivatives). Unfortunately, the use of these metallodrugs are accompanied by severe adverse side-effects. Additionally, the evolution of resistant cancer cell sub-types has rendered many of these highly efficacious platinum drugs, ineffective. Utilizing alternative platinum group metals (PGMs), such as iridium and ruthenium, and incorporating known pharmacophoric scaffolds within the framework of a target compound, has been a favourable approach toward combating these obstacles, while further enhancing the pharmacological activity of potential drug candidates. The increased popularity and success of metal-containing compounds as pharmaceutical agents has prompted investigations into the pharmacological activity of a different class of metal-based compounds, supramolecular coordination complexes (SCCs). Such complexes have been extensively investigated for their anticancer activity, with many PGM SCCs displaying activity greater than or comparable to available clinical chemotherapeutic drugs. Interestingly, however, no studies have investigated the antiplasmodial activity of SCCs, a field that warrants further exploration. Due to the pharmacological activity associated with the quinoline scaffold, this pharmacophore was incorporated into a newly designed N,N'-ditopic ligand (L). The quinoline-containing ligand (L), synthesized via a Suzuki cross-coupling reaction, was reacted with either [Ir(Cp*)(μ-Cl)Cl]2 or [Ru(pcymene)(μ-Cl)Cl]2, via a bridge splitting reaction, to yield the corresponding precursor binuclear complexes. The subsequent iridium(III) and ruthenium(II) metallarectangles were synthesized, as their triflate salts, via coordination-driven self-assembly. All of the compounds were fully characterised using an array of spectroscopic (1H, 13C, DOSY NMR, and FT-IR spectroscopy) and analytical (ESI-MS and melting point analysis) techniques. The known, corresponding 4,4'-bipyridine analogues were also synthesized to evaluate the pharmacological effects of incorporating the quinoline pharmacophore into the framework. Single crystal X-ray diffraction confirmed the proposed molecular structure of the iridium binuclear complex, [{IrCl2(Cp*)}2(μ-L)], and DFT calculations support the proposed structure of metallarectangle [{Ir(μ-Cl)(Cp*)}4(μ-L)2](OTf)4. All of the synthesized compounds were evaluated for their in vitro antiplasmodial activity against the chloroquine-sensitive (NF54) and multidrug-resistant (K1) strains of the malaria parasite, Plasmodium falciparum, which is the most virulent species within the genus Plasmodium. In general, incorporation of the quinoline scaffold enhanced the activity at least two-fold, compared to the corresponding 4,4'-bipyridyl analogues. Metal complexation increased the in vitro antiplasmodial activity of the uncoordinated ligands (both L and 4,4'-bipyridine) up to 50-fold, in both the NF54 and K1 strains of the parasite. An increase in the nuclearity of the system resulted in a further increase in activity of up to 12-fold. Furthermore, the resistance indices of the synthesized compounds suggest that they largely retain their activity in the resistant strain of the parasite. Considering that quinoline-containing compounds are generally known to inhibit haemozoin formation, to gain insight into a possible mechanism of action, the quinoline-containing ligand L and selected metallarectangles, [{Ir(Cp*)}4(μ-ƞ 2 -ƞ 2 -C2O4)2(μ-L)2](OTf)4 and [{Ru(p-cymene)}4(μ-ƞ 2 -ƞ 2 - C2O4)2(μ-L)2](OTf)4, were tested for their β-haematin inhibitory activity. Both of the tested metallarectangles displayed promising β-haematin inhibitory activity, with the iridium metallarectangle inhibiting β-haematin formation to almost the same extent as CQ. Furthermore, the new quinoline-containing compounds were evaluated for their in vitro anticancer activity in MCF-7 and MDA-MB-231 breast cancer cell lines. The preliminary cytotoxic screen, in the MCF-7 cell line, revealed that ligand L and metallarectangle [{Ir(μ-Cl)(Cp*)}4(μ-L)2](OTf)4 displayed superior activity to cisplatin. Interestingly, despite being near inactive in the MCF-7 cell line, [{Ru(pcymene)}4(μ-ƞ 2 -ƞ 2 -C2O4)2(μ-L)2](OTf)4 displayed the greatest activity in the triple-negative MDA-MD231 cell line, at 10 μM, exceeding the 45% reduction in cell viability caused by cisplatin at the same concentration. Upon evaluation in a multidose screen, ligand L and metallarectangle [{Ir(μCl)(Cp*)}4(μ-L)2](OTf)4 displayed antiproliferative activity almost two-fold greater than cisplatin, in the MCF-7 cell line, while [{Ru(p-cymene)}4(μ-ƞ 2 -ƞ 2 -C2O4)2(μ-L)2](OTf)4 was over two-times more active than cisplatin in the MDA-MB-231 cell line. Finally, the aforementioned compounds were evaluated for their cytotoxicity against the non-tumorigenic MCF-12A cell line. The selectivity indices of these compounds suggest that they demonstrate increased selectivity toward cancerous cells, over healthy cells.